Exploring the Use of Word Chain Game for Vocabulary Enrichment in English Language Classroom - Fika Hawi Lestari; Fahmy Imaniar; Ita Eka Oktaviani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
One of the greatest challenges of learning English as foreign language is learning new words. The issue is that many EFL students cannot memorize new words when they are introduced with the help of rote and repetition, which can decrease motivation and interest in the process. The given research project will investigate the application of the Word Chain game as a vocabulary learning strategy in classrooms of the Indonesian junior high school. In particular, it will also explore the process of implementing the game by a teacher, and the response of students to the use of this game in classroom activities. The design used in the study was a qualitative case study design, which conducted one English teacher and 30 seventh-grade students in a junior high school in Surabaya, which is a public school. Teacher interviews, student questionnaires and classroom documentation were used to gather data which was analyzed in a thematic manner. The results have shown that the Word Chain game encourages active involvement, advances vocabulary memory and motivates students. These findings add value to the body of game-based learning research since they demonstrate that even low-tech traditional games can be useful in the EFL classroom to develop more interactive and cooperative learning activities in vocabulary.